Advanced Sensing and Image Processing Techniques for Healthcare Applications - Abolghasemi, Vahid; Anisi, Hossein; Ferdowsi, Saideh (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue aims to attract the latest research and findings in the design, development and experimentation of healthcare-related technologies. This includes, but is not limited to, using novel sensing, imaging, data processing, machine learning, and artificially intelligent devices and algorithms to assist/monitor the elderly, patients, and the disabled population.